2018
DOI: 10.5935/0103-507x.20180060
|View full text |Cite
|
Sign up to set email alerts
|

Use of vasopressin in the treatment of refractory septic shock

Abstract: ObjectiveTo evaluate the short-term evolution of patients with septic shock refractory to norepinephrine treated with vasopressin in an intensive care unit of a university hospital.MethodsAn unmatched retrospective study (case series) was performed. Clinical, laboratory, and anthropometric data were collected from patients who received vasopressin infusion for treatment of catecholamine-refractory shock from December 2014 to June 2016. For the assessment of severity, APACHE II and SOFA scores were used. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
6
0
3
Order By: Relevance
“…The high mortality rate that was found (80.8%) is common in refractory shock and corroborates other studies, demonstrating the severity of these cases. Comparatively, in the study by Kny et al 2018, 75% of deaths were observed within 72 hours and 86.2% within 30 days, in 80 cases of refractory septic shock, the majority with a hospital stay of up to 10 days (Kny et al, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…The high mortality rate that was found (80.8%) is common in refractory shock and corroborates other studies, demonstrating the severity of these cases. Comparatively, in the study by Kny et al 2018, 75% of deaths were observed within 72 hours and 86.2% within 30 days, in 80 cases of refractory septic shock, the majority with a hospital stay of up to 10 days (Kny et al, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…Role and adverse effects of VP are described in detail in the text [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Spg-symmetrical Peripheral Gangrenementioning
confidence: 99%
“…According to a study by Kny et al [ 27 ], VP usage may raise blood pressure and decrease the need for catecholamines in septic shock patients who are resistant to intravenous fluids and other treatments; leading to an indirect reduction in the detrimental effects of catecholamines on renal failure and arrhythmias [ 27 ]. The reason not to use NE in higher doses might be the insensitivity of adrenergic receptors in patients with septic shock which diverts NE to work on nonspecific loci leading to adverse effects such as undesirable hemodynamic effects, also enhanced coagulation, reduced innate and adaptive immunity, and increased bacterial replication and virulence [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…P <0,05 değeri istatistiksel açıdan anlamlı kabul edildi. (13,17). Sepsisteki yüksek ölüm hızı, tedavi kalitesi ve hastalığın karmaşık yapısı ile ilgilidir (15).…”
Section: İstatistiksel Analizunclassified
“…Bu nedenle septik şoklu hastalarda perfüzyonun arttırılması, mikro dolaşımın izlenmesi ve yönetilmesi önemlidir (18). Bu amaçla, septik hastalarda, kan basıncını yeniden sağlamak ve organ işlevini düzeltmek için hacim genişlemesi yeterli olmadığında inotrop desteği yapılmalıdır (13,14,16). Ayrıca, sepsisteki hastalarda yakın şok takibi, şokun erken tanısı ve tedavisi için bazı parametrelere ihtiyaç vardır.…”
Section: İstatistiksel Analizunclassified